Evaluation of avulsed primary incisor in 3-year-old girl with hypophosphatasia who received enzyme replacement therapy. Issue 3 (December 2018) - Okawa, Rena; Miura, Jiro; Kokomoto, Kazuma; Nakano, Kazuhiko
Abstract: Hypophosphatasia (HPP) is an inherited skeletal disease with features of hypomineralization of bone and early exfoliation of primary teeth due to disturbed cementum formation. Recent introduction of enzyme replacement therapy has reduced mortality in severe cases, though the effects of that treatment on dental manifestations remain unknown. We examined an avulsed primary incisor in a 3-year-old female diagnosed with perinatal HPP who underwent enzyme replacement therapy from 1 day after birth and report our findings.